2012
DOI: 10.1007/s00381-012-1892-8
|View full text |Cite
|
Sign up to set email alerts
|

Subependymal nodules and giant cell tumours in tuberous sclerosis complex patients: prevalence on MRI in relation to gene mutation

Abstract: TSC patients with SENs are more likely to present with SGCT than those without SENs, in particular for TSC2 mutation carriers. The SGCT growth rate may be missed if based on the diameter instead of on the volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Nonetheless, the numbers of abnormalities identified in our cohort were mostly similar or higher than those reported in previous studies. 9,10,24 The number of RMLs in our cohort was lower than that reported in another cohort, possibly because we did not use diffusion tensor imaging or three-directional scans. 32 In summary, we compared TSC brain pathology to genotype.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Nonetheless, the numbers of abnormalities identified in our cohort were mostly similar or higher than those reported in previous studies. 9,10,24 The number of RMLs in our cohort was lower than that reported in another cohort, possibly because we did not use diffusion tensor imaging or three-directional scans. 32 In summary, we compared TSC brain pathology to genotype.…”
Section: Discussioncontrasting
confidence: 38%
“…23 The larger number of calcified SENs in the TSC2 group could also be clinically relevant, as calcified SENs are more likely to develop into a SEGA. 24 Two patients in our cohort were mosaic. Both had bilateral TSCrelated abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…However, only IS and epilepsy are strongly associated with TSC2 mutations, whereas MR and neurocognitive impairment are linked to different types and location of TSC1 and TSC2 germline mutations, rather than to the specific gene in which the mutation occurred (van Eeghen et al, 2013). Similarly, the presence of SENs and SEGAs is not significantly associated with either gene mutation (Michelozzi et al, 2013), and variability in TSC symptoms has been reported in individuals with identical TSC mutations (Rok et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…SEGAs are the most common brain tumors occurring in up to 20 % of the TSC patients, usually in the first two decades of life [6, 23, 35]. They are typically located on the surface of the lateral ventricle of the brain, and thus, while growing, they extend into the lateral ventricle and can obstruct the foramen of Monro and flow of CSF, causing hydrocephalus [8, 10].…”
Section: Discussionmentioning
confidence: 99%